2020
DOI: 10.1186/s13104-019-4875-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced quantitative urine culture technique, a slight modification, in detecting under-diagnosed pediatric urinary tract infection

Abstract: Objectives: The pediatric urinary tract infection (UTI) often remains under-diagnosed or neglected owing to non-specific clinical presentations, patients failing to describe the actual situation and of clinical practice in diagnosis. The study was aimed to determine the etiologies of UTI in children with enhanced quantitative urine culture (EQUC) technique. Results:Of enrolled 570 pediatric urine samples, the significant growth positivity was higher in EQUC 92 (16.15%) compared to standard urine culture (SUC) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…About half of the uropathogens in the UTI cohort were missed by standard urine culture; additionally, the threshold of 10 5 CFU/mL would not report a predominant organism in numerous patients with a clinical UTI in this cohort. Another study of 570 pediatric patients at a hospital in Nepal with symptoms concerning for a UTI found that an EQUC picked up significantly more known uropathogenic microbes than standard culture, including Candida albicans , Provedencia retergerii , and Morganella morganii [ 51 ]. In the same study, EQUC also identified all probable uropathogens including extended-spectrum beta-lactamase (ESBL) producers, multi-drug resistance (MDR) and extensive drug-resistant (XDR) organisms that would be overlooked by SUC [ 51 ].…”
Section: Expanded Quantitative Urine Culture (Equc)mentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the uropathogens in the UTI cohort were missed by standard urine culture; additionally, the threshold of 10 5 CFU/mL would not report a predominant organism in numerous patients with a clinical UTI in this cohort. Another study of 570 pediatric patients at a hospital in Nepal with symptoms concerning for a UTI found that an EQUC picked up significantly more known uropathogenic microbes than standard culture, including Candida albicans , Provedencia retergerii , and Morganella morganii [ 51 ]. In the same study, EQUC also identified all probable uropathogens including extended-spectrum beta-lactamase (ESBL) producers, multi-drug resistance (MDR) and extensive drug-resistant (XDR) organisms that would be overlooked by SUC [ 51 ].…”
Section: Expanded Quantitative Urine Culture (Equc)mentioning
confidence: 99%
“…Another study of 570 pediatric patients at a hospital in Nepal with symptoms concerning for a UTI found that an EQUC picked up significantly more known uropathogenic microbes than standard culture, including Candida albicans , Provedencia retergerii , and Morganella morganii [ 51 ]. In the same study, EQUC also identified all probable uropathogens including extended-spectrum beta-lactamase (ESBL) producers, multi-drug resistance (MDR) and extensive drug-resistant (XDR) organisms that would be overlooked by SUC [ 51 ]. While these studies show promise in improved detection of uropathogens, including those that may be MDR or XDR, future studies following the treatment and potential symptomatic resolution in patients with previously “uncultivated” microbes are necessary.…”
Section: Expanded Quantitative Urine Culture (Equc)mentioning
confidence: 99%
“…Culture-positive asymptomatic bacteriuria is commonly reported in women and older adults; although, this is sometimes deemed "contamination" based on bacterial counts < 10 5 [2]. Culture-negative symptomatic urinary tract infections (UTIs) are also common, and can, in some cases, be attributed to fastidious organisms that fail to grow using standard urine culturing (SUC) techniques [2][3][4][5][6][7][8]. More recently, culture-independent next-generation sequencing of urine and enhanced quantitative urine culture (EQUC) has revealed the presence of bacteria in >90% of individuals-including those with and without UTIs and from urine collected via free-catch, transurethral catheter, or suprapubic aspirates [5][6][7][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Culture-positive asymptomatic bacteriuria is commonly reported in women and older adults; although, this is sometimes deemed “contamination” based on bacterial counts < 10 5 (Kass, 1962). Culture-negative symptomatic urinary tract infections (UTIs) are also common, and can, in some cases, be attributed to fastidious organisms that fail to grow using standard urine culturing (SUC) techniques (Dune et al, 2017; Kass, 1962; Maskell et al, 1979; Maskell, 2010; Price et al, 2016; Thapaliya et al, 2020; Thomas-White et al, 2018). More recently, culture-independent next-generation sequencing of urine and enhanced quantitative urine culture (EQUC) has revealed the presence of bacteria in >90% of individuals – including those with and without UTIs and from urine collected via free-catch, transurethral catheter, or suprapubic aspirates (Chen et al, 2018; Hilt et al, 2014; Pearce et al, 2014; Pohl et al, 2020; Price et al, 2020, 2016; Thapaliya et al, 2020; Thomas-White et al, 2018; Wolfe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%